Gender differences in characteristics, treatment and outcomes in ST elevation myocardial infarction patients in four European countries. (14th October 2021) - Hellgren, T; Blondal, M; Ainla, T; Jortveit, J; Eha, J; Loiveke, P; Marandi, T; Saar, A; Veldre, G; Lewinter, C; Halvorsen, S; Ferenci, T; et al.
Abstract: Introduction: Women receive less evidence-based care than men and have higher mortality after myocardial infarctions than men. But it is not known how the gender difference in risk factors, treatments and outcomes differs between European countries. Purpose: In order to investigate the gender differences in European countries with different economic predispositions we aimed to describe and compare baseline characteristics, in-hospital management, medications at discharge and death outcomes of man and woman ST-elevation infarction (STEMI) patients following routine clinical practice in Sweden, Norway, Hungary and Estonia. Methods: The study population is patients over the age of 18 with STEMI who were treated in hospital 2014–2017 (for Norway between 2013–2016) and registered in one of the national myocardial infarction registers. Patients with non-ST elevation infarction and unstable angina were excluded. Risk factors, hospital treatment, and prescription medications were obtained from the national myocardial infarction registries from each country. Mortality in-hospital, after 30 days and after 1 year, was obtained from national death registers. Results: Women were on average older, had more comorbidities and higher mortality in hospital, after 30 days and one year after hospitalization. Women received coronary angiography, percutaneous coronary intervention, left ventricular ejection fraction assessment and evidence-based drugs to a lesser extent than men. Conclusions: The study illustrates that there are differences in characteristics, management, treatments and outcomes between men and women in all of the studied countries no matter economic predispositions. Generally, women are treated with guideline recommended therapy to a lesser extent than men in the studied countries. FUNDunding Acknowledgement: Type of funding sources: None.